2020
DOI: 10.1039/d0ra05838f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective sulfoxidation using Streptomyces glaucescens GLA.0

Abstract: Application of Streptomyces glaucescens as a whole-cell oxidative biocatalyst without using an external cofactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The latter is a natural product isolated from Juglans mandshurcia Maximowicz, which has anti-leishmanial and antidiabetic activities. 70 Among different cultures, S. griseus NRRL B8090 gave the highest conversion, and the subsequent trials with the whole cells for a preparative scale conversion of 150 mg naphthalene resulted in 81 mg of the pure product aer 72 h. Furthermore, another derivative, 2-methyl-1,4naphthoquinone (31), was converted to the corresponding hydroxyl compounds (32) with the whole cells of the same Streptomyces strain (Scheme 10). 70 Gurram et al (2009) reported the use of S. griseus NCIM 2622, among ve tested actinomycetes, to catalyze the oxidation of meloxicam ( 33), a non-steroidal anti-inammatory drug, into two metabolites: 5-hydroxymethyl meloxicam (34) and trace amounts of 5-carboxy meloxicam (35) (Scheme 11), with a higher biological activity.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter is a natural product isolated from Juglans mandshurcia Maximowicz, which has anti-leishmanial and antidiabetic activities. 70 Among different cultures, S. griseus NRRL B8090 gave the highest conversion, and the subsequent trials with the whole cells for a preparative scale conversion of 150 mg naphthalene resulted in 81 mg of the pure product aer 72 h. Furthermore, another derivative, 2-methyl-1,4naphthoquinone (31), was converted to the corresponding hydroxyl compounds (32) with the whole cells of the same Streptomyces strain (Scheme 10). 70 Gurram et al (2009) reported the use of S. griseus NCIM 2622, among ve tested actinomycetes, to catalyze the oxidation of meloxicam ( 33), a non-steroidal anti-inammatory drug, into two metabolites: 5-hydroxymethyl meloxicam (34) and trace amounts of 5-carboxy meloxicam (35) (Scheme 11), with a higher biological activity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, cloning and expression of the enzymes involved the oxidation reactions will be useful for understanding the enzyme features for activity and stability, and for designing better enzymes. Selective heteroatom oxidations have just been reported for some Streptomyces species, 32,88 in addition to specic oxidation of unactivated C-H bonds, 78,80 which opens up the possibilities for further studies on identifying the enzymes involved in such species. Development of expression hosts for the genes from Streptomyces species is yet another aspect that would be needed for increasing the utilization of these important biocatalysts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations